Digital Da’wah via Social Media and Its Impact on Islamic Religious Education Learning Motivation among Informatics Engineering Students at Universitas Pelita Bangsa - Badruzzaman, Aceng; Hisniati, Sally Badriya; Ermanto, Ermanto; Najamuddin, Muhammad (International Journal Corner of Educational Research, 2025)
The rapid development of digital technology and the widespread use of social media have transformed the landscape of Islamic religious communication and learning in higher education. This study aims to examine the effectiveness of social media–based digital da’wah in influencing students’ learning motivation in Islamic Religious Education (IRE) among Informatics Engineering students at Universitas Pelita Bangsa. This study employed a descriptive quantitative approach with a survey method. The population consisted of Informatics Engineering students in semesters 1, 3, and 5, with a sample of 108 respondents selected using purposive and simple random sampling techniques. Data were collected using a structured questionnaire with a five-point Likert scale. The data were analyzed using descriptive statistics, reliability testing, and simple linear regression. The results show that the digital da’wah variable and learning motivation variable demonstrated excellent reliability, with Cronbach’s Alpha values of 0.952 and 0.944, respectively. The regression analysis indicated that digital da’wah has a significant positive effect on learning motivation (β = 0.973, p < 0.001), with a coefficient of determination of R² = 0.718, indicating that 71.8% of the variance in learning motivation is explained by digital da’wah. These findings suggest that social media–based digital da’wah plays a strategic role in enhancing students’ motivation to learn Islamic Religious Education. Integrating digital da’wah content into formal learning strategies can improve students’ engagement and support the internalization of Islamic values in higher education.